2005
DOI: 10.1118/1.1951427
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of dose‐volume and dose‐wall histograms for rectal toxicity following 3D‐CRT in prostate cancer

Abstract: The purpose of this paper is to determine the correlation between dose-volume histogram (DVH) and dose wall-histogram (DWH) in the evaluation of rectal complications for prostate cancer patients treated with three-dimensional conformal radiotherapy (3D-CRT). A retrospective analysis of DVHs and DWHs of a subset of 25 prostate cancer patients treated with 3D-CRT was performed. For every patient the rectum and the rectal wall (inner and outer surface) were contoured. Median ICRU radiation dose of 79.4 Gy was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…dose-surface histograms, or measures of dose to the circumference of tubular structures). This can be mitigated if the corresponding response rate function for a standard variable is also supplied (see reference (23): table 2, and figures 3 and 4) or if the relationship between the variables is well understood (see reference (24): figure 4).…”
Section: Requirements For Future Quantec Effortsmentioning
confidence: 99%
“…dose-surface histograms, or measures of dose to the circumference of tubular structures). This can be mitigated if the corresponding response rate function for a standard variable is also supplied (see reference (23): table 2, and figures 3 and 4) or if the relationship between the variables is well understood (see reference (24): figure 4).…”
Section: Requirements For Future Quantec Effortsmentioning
confidence: 99%
“…There is some disagreement in the literature regarding the similarity of the different histogram types. Garcia-Vicente et al (2005) claim that the DVH is found to be similar to the DWH for most patients, while Meijer et al (1999) found that a manually outlined DWH, an auto-generated DWH with variable wall thickness, and NDSH were all similar, but each disagreed with the whole-rectum DVH. Lu et al (1995) found that the ranking of different plans may change depending on the use of DSH or whole-rectum DVH.…”
Section: Introductionmentioning
confidence: 99%
“…Típicamente, el tamaño del margen se expresa como un parámetro sencillo, su ancho, que está basado en estudios de movimientos de órganos en grupos de pacientes, aunque a veces este valor no es constante y se reduce alrededor de estructuras críticas. Por ejemplo, en el cáncer de próstata, el tamaño del margen se reduce casi a la mitad alrededor del recto [44] para limitar la toxicidad. La construcción más simple del PTV se basa en dos hipótesis que parten de las limitaciones técnicas en la planificación del tratamiento.…”
Section:  Organ At Riskunclassified
“…La radioterapia tridimensional conformada (3D conformal radiotherapy, 3D-CRT) ha reemplazado esencialmente a la radioterapia convencional en la gestión de cáncer de próstata [44]- [46]. El éxito de 3D-CRT en el tratamiento del cáncer de próstata es el resultado de múltiples factores, incluyendo las relaciones dosis-respuesta favorables de la técnica, la habilidad de reducir la radiación a los tejidos sanos colindantes, la relativa inmovilidad del órgano (típicamente alrededor de un centímetro), y la gran prevalencia de la enfermedad [47].…”
Section: I23 Radioterapia Tridimensional Conformadaunclassified